I don't know what I am doing because I am doing everything: perceptions and experiences of nurses about HIV counselling and testing among children in Free State Province, South Africa. (26th May 2016) - Olaleye, Abiola O.; Tsibolane, Yolisa; Van-Turha, Lydia; Monareng, Sibongile; Chikobvu, Perpetual; Boleme, Mohlouoa Sam; Serenata, Celicia
ABSTRACT: Although HIV/AIDS constitute a significant health burden among children in South Africa, testing and counselling of exposed children are inadequate. It is therefore imperative that factors relating to paediatric HCT services offered by health workers are examined. This study was conducted to explore and describe the perceptions and experiences of trained professional nurses regarding HIV counselling and testing among children. We conducted six focus group discussions among trained professional nurses in health facilities in a district in Free State Province, South Africa. All verbatim transcripts were analysed with a thematic approach and emergent codes were applied. Forty-seven trained professional nurses participated in the study and two of them were males. The age of the participants ranges from 38 to 60 years while the median age was 50 years. Most participants in the focus groups explained how HCT occurs during regular health talks and that lay counsellors are doing most of the counselling. While a few participants thought that children should not be bothered with HCT, most of them seek consent from caregivers for HIV test for children. While children whose parents are negative are usually not tested, most children are tested only when they become ill. Identified barriers to HCT among children include refusal of consent, work overload, lack of encouragement, and poor record keeping. Participants recommended improvement of issues relating to community mobilization and increasing trained staff strength for optimal paediatric HCT service delivery. Developing guidance and policies with respect to obtaining consent, recruiting more health providers, and addressing structural issues in the society to reduce stigma and discrimination were identified as key priority issues by majority of the participants. The perspectives of these participants who provide paediatric HCT services offer vital insight which may be useful to inform policy interventions.